Assessing Yield, Quality and Nutrient Use Efficiency of Rice (Oryza sativa L.) with Agronomic Iron Bio-fortification - , Seerat Jan; , Zahida Rashid; , Tanveer Ahmad Ahngar; , Raies A Bhat; , Aamir H Mir; , Sabina Nasseer; , Razia Gul (Archives of Current Research International, 2024)
To assess the impact of foliar iron nutrition on the yield, quality, and nutrient utilization of rice variety SR-4 (Oryza sativa L.), a field experiment was conducted during the Kharif season of 2019 at the Crop Research Farm of the Division of Agronomy, Faculty of Agriculture, Sher-e-Kashmir University of Agricultural Sciences and Technology of Kashmir Wadura. The experiment involved four levels of iron (0.25%, 0.5%, 0.75%, and 1%) applied through three different sources (FeSO4. 7H2O, Na-Fe EDTA, and Ferric chloride), along with a control, arranged in a randomized complete block design with three replicates. Results showed that applying FeSO4.7H2O at 1% significantly increased crop growth rate (CGR), relative growth rate (RGR), net assimilation rate (NAR), grain yield, straw yield, biological yield, iron content in brown rice and straw, as well as iron uptake. However, iron chelate at 0.75% demonstrated the highest harvest index. Iron chelate at 0.25% exhibited the highest iron use efficiency, while FeSO4.7H2O at 1% resulted in the highest protein content. No significant difference was observed among treatments regarding amylose content. Consequently, it was determined that applying FeSO4.7H2O at 1% could be a promising strategy for agronomic biofortification with iron to improve both yield and quality of rice in the temperate conditions of Kashmir valley.